Wavefunction Correction Scheme for Non Fixed-Node Diffusion Monte Carlo (Journal of Atomic and Molecular Sciences, 2018)
Wavefunction correction scheme, which was developed as a variance reduction tool for the pure and fixed-node diffusion Monte Carlo (DMC) computations by Anderson and Freihaut, is applied to the DMC computations of fermions without using the fixed-node constraint. This technique is found to be suitable for the non fixed-node calculations because of the significant decreases observed in the computation efforts in the benchmark computations for calculating results with certain statistical error values.